Occurrence of Artemisia chinensis (L.) plant (Asteraceae) in the Northeastern (Gilgit-Baltistan) Pakistan: Evidence From Molecular Phylogeny of nrDNA and cpDNA Sequences: Occurrence of Artemisia chinensis in Gilgit-Baltistan Pakistan - Hussain, Adil (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Artemisia chinensis L. referred as Crossostephium chinensis (L.) Makino in the Flora of China is a rare and conceivably threatened plant species with an unclear origin in Asia. The species has been acknowledged so far from some islands of Taiwan. However, as it is extensively cultivated for ornamental and medicinal purposes in Japan, China, and the Philippines, it is still challenging to delimit its native range. This study confirms the presence of A. chinensis from Northern (Gilgit-Baltistan) Pakistan using molecular phylogenetic analysis and by assessing its distribution. The species were found in one site in the Skardu District of GB Pakistan and phylogenetic analysis indicated a close resemblance of the collected A. chinensis from the Skardu region with species of subgenus Pacifica of the genus Artemisia reported globally. According to the outcomes of the present study, it is proposed that broader field surveys should be conducted to acknowledge the distribution of A. chinensis plant from other districts of GB and cities of Pakistan as well. It is proposed that A. chinensis plant is present in North Pakistan and this plant should be mentioned and retained as rare species in the flora of Pakistan.